PENGARUH KOMBINASI KOMPOS BONGGOL PISANG (Musa balbissiana Colla) DAN FUNGI MIKORIZA ARBUSKULAR PADA MEDIA TUMBUH TERHADAP PERTUMBUHAN SEMAI CEMPAKA (Elmerrillia ovalis (Miq) Dandy) - Oktaviani, Eka Putri; Yusran, Yusran; Umar, Husein; Rahmawati, Rahmawati (Jurnal Warta Rimba, 2021)
The application of arbuscular mycorrhizal fungi and compost is one of the environmentally friendly technologies to improve the fertility of the planting media so that the results of the seeds are higher of quality. Banana weevil or banana stem is an organic material that has several macro and micro nutrient content, for example N, P and K, and contain chemical compounds in the form of carbohydrates that can stimulate the growth of microorganisms in the soil. Furthermore, arbuscular mycorrhizal fungi (AMF) can increase nutrient uptake from the soil into the roots. The purpose of this research was to determine the effect of the addition of banana weevil compost (Musa balbissiana Colla) and arbuscular mycorrhizal fungi on growing media on the growth of cempaka seedlings (Elmerrillia ovalis (Mig) Dandy). The result of this research showed that the combination of banana weevil compost and arbuscular mycorrhizal fungi on growing media significantly influences the growth of leaf number and dry weight, but no significant effect on growth in height, diameter and wet weight. The combination of banana weevil + soil (P1) compost treatment on growth media gave the growth of cempaka seedlings (Elmerrillia ovalis (Mig) Dandy) better than other treatments. The treatment of banana weevil + soil compost (P1) gives the best effect on all parameters, which is the increase in diameter with an average of 0.70 mm, height increase with an average of 2.70 cm, increase in the number of leaves of 1.70 strands, wet weight with an average of 2.90 g, dry weight with an average of 0.60 g.Keywords: compost,arbuscular mycorrhizal fungi, Elmerrillia ovalis (Mig) Dandy